Cultural Management in Costa Rica: definition and scope - Alpízar Valverde, Nicolas (2020)
This text presents a specific descriptive and conceptual framework for contemporary Cultural Management in Costa Rica. To achieve that, it develops a critical review of concepts, a historical overview and a reclassification proposal; along by an empirical consultation. It begins with the review of the two conceptual aspects of Cultural Management. At the beginning, the evolution from classical administration to more contemporary management is reviewed. Then, given the extensive discussion on the concept of Culture, two meanings are contrasted, one restricted and one broad, which coexist both in international conventions and in daily practice. In order of clearing ambiguities, a categorization of cultural assets is proposed, instead of the traditional use of Cultural Heritage. Subsequently, it analyzes the Costa Rican Cultural Management from the theory and through a historiographic revision. Due to direct consultation with people who practice it, the objects and practices that professionals practice on national land are described. The author ends with his reflections and, far from issuing closed criteria, he hopes to promote discussion and encourage future research.